2013
DOI: 10.1017/s0007114513001943
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of germanium-containingSpirulinain rats withd-galactosamine- and lipopolysaccharide-induced hepatitis

Abstract: In the present study, the protective effects of dietary Spirulina (SP) and germanium-containing Spirulina (GeSP) were compared in rats with liver injury induced by an intraperitoneal injection of D-galactosamine and lipopolysaccharide (GalN/LPS). Wistar rats were fed one of the following diets: the basal diet (GalN/LPS-CON group; n 6), the basal diet supplemented with 5 % SP or GeSP (GalN/LPS-SP and GalN/LPS-GeSP group, respectively; n 7 each). After administering these diets for 7 d, each rat was intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Використання органічного Ge у поєднанні з рафінозою стимулювало мікробіологічні процеси у травному каналі щурів [58]. Поєднання Ge-вмісної спіруліни з d-галактозаміном і ліпополісахаридами зумовлювало гепатопротекторну дію у щурів [99].…”
Section: вплив органічних сполук Ge хімічного синтезу на організм тваринunclassified
“…Використання органічного Ge у поєднанні з рафінозою стимулювало мікробіологічні процеси у травному каналі щурів [58]. Поєднання Ge-вмісної спіруліни з d-галактозаміном і ліпополісахаридами зумовлювало гепатопротекторну дію у щурів [99].…”
Section: вплив органічних сполук Ge хімічного синтезу на організм тваринunclassified
“…Spirulina has been used as an antioxidant protector in different toxicological models that involved the kidney. [8][9][10][11][12] The nephroprotective activity of Spirulina and its components is associated with the antioxidant capacity of them. Spirulina contains vitamins (A, B, C, and E), essential amino acids, and fatty acids; as well as another pigment as carotenoids, chlorophylls, and phycobiliproteins as phycocyanin that acts as nucleophilic compounds and they can neutralize free radical and reactive species.…”
Section: Introductionmentioning
confidence: 99%
“…The model was widely used to explore the pathogenesis of fulminant hepatitis and develop novel liver-protective reagents [7]. Previous studies showed that LPS/GalN induced inflammatory cytokines TNF-α, IL-1β, and IL-6 production in mice model of hepatic failure [8,9]. These inflammatory cytokines contributed to liver cells necrosis and hepatic failure.…”
Section: Introductionmentioning
confidence: 99%